Smart Apps Creator (SAC) Assisted Comic Media Development in Optimizing Visual Spatial Intelligence - Asri Wahyuni; Supratman Supratman; Puji Lestari (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2023)
This study aims to produce SAC-assisted comic media and analyze the effectiveness and quality of using comics media to optimize students' visual-spatial intelligence. This research is a Research and Development (R&D) research using a 4D development model, which includes four stages: define, design, develop, and disseminate. In the